On the Connection of Monthly Mean of Some Simple Thermal Indices and Tourism Climate Index with the Mortality of the Population of Tbilisi City Apropos of Cardiovascular Diseases - Amiranashvili, Avtandil G.; Japaridze, Nino D.; Khazaradze, Ketevan R. (Journals of Georgian Geophysical Society, 2018)
The comparative analysis of the connection of eight simple thermal indices and Tourism Climate Index (TCI) with the monthly mortality of the population of Tbilisi city apropos of cardiovascular diseases is represented. The values of simple thermal indices were calculated with the use of mean monthly and mean monthly for 13 hours data of meteorological elements. Between all studied simple thermal indices practically direct functional connection with the coefficient of linear correlation not lower than 0.86 is observed. The connection of simple thermal indices with the TCI is nonlinear and takes the form of third power polynomial. The possibility of using the standard scales and categories of the indicated indices as the bioclimatic indicator in monthly time scale is studied. As a whole, all indices adequately correspond to the degree of the bioclimatic comfort of environment for the people - with an increase in the level of comfort the mortality diminishes. Most representative for this purpose is Missenard air effective temperature in 13 hours